Justice and the politics of capabilities: Sen, Nussbaum and Navarro - Hrvoje Cvijanović (Anali Hrvatskog Politološkog Društva, 2019)
Linking the idea of justice with human dignity through the 'politics of capabilities' is a recent theoretical project advanced by Amartya Sen and Martha Nussbaum and inspired by the shortcomings of Rawls's understanding of justice. Rawls's view on the redistribution of resources or primary goods has nothing to say about someone's capabilities to use these goods, so the idea of capabilities becomes central since it is focused on the way of life a person has a reason to value. The article discusses Sen and Nussbaum's development of the capabilities approach and their criticism of Rawls's fundamental premises about justice. Although the capabilities approach attempts to rectify injustices that Rawls failed to address properly, there are limitations of that approach as well. At the end, it is shown that capabilities are valued in relation to their contribution to the system of production – having more capabilities enhances someone's socio-economic position within the given structure – but this does not question the existing power relations and the very structure that perpetuate inequalities. Hence, the author agrees with the line of criticism that invokes the issue of power relations provided by Vicente Navarro, yet extending this criticism to Rawls's theory of justice for not fundamentally questioning the power relations inherent in the institutions reproducing social injustices.